The potential interaction between medical treatment and radioiodine treatment success: A systematic review - Zannat, Riazul; Lee, Jonathan; Muzaffar, Jameel; Read, Martin L.; Brookes, Katie; Sharma, Neil; Boelaert, Kristien; McCabe, Christopher J.; Nieto, Hannah R. (Frontiers in Endocrinology, 2023)
ABSTRACT Introduction Radioactive iodine (RAI) therapy is a critical component in the post-surgical management of thyroid cancer patients, as well as being a central therapeutic option in the treatment of hyperthyroidism. Previous work suggests that antithyroid drugs hinder the efficacy of RAI therapy in patients. However, the effects of other background medications on RAI treatment efficacy have not been evaluated. Therefore, we performed a systematic review and meta-analysis investigating the potential off-target effects of medication on RAI therapy in patients with thyroid cancer and hyperthyroidism. Methods Systematic review and meta-analysis according to the 2020 PRISMA guidelines. Databases searched: MEDLINE, EMBASE and Cochrane Library for studies published between 2001 and 2021. Results Sixty-nine unique studies were identified. After screening, 17 studies with 3313 participants were included. One study investigated thyroid cancer, with the rest targeted to hyperthyroidism. The majority of studies evaluated the effects of antithyroid drugs; the other drugs studied included lithium, prednisone and glycididazole sodium. Antithyroid drugs were associated with negative impacts on post-RAI outcomes (n = 5 studies, RR = 0.81, p = 0.02). However, meta-analysis found moderate heterogeneity between studies (I2 = 51 %, τ2 = 0.0199, p = 0.08). Interestingly, lithium (n = 3 studies), prednisone (n = 1 study) and glycididazole (n = 1 study) appeared to have positive impacts on post-RAI outcomes upon qualitative analysis. Conclusion Our systematic review strengthens previous work on antithyroid medication effects on RAI, and highlights that this field remains under researched especially for background medications unrelated to thyroid disease, with very few papers on non-thyroid medications published.